2019
DOI: 10.1371/journal.pone.0211809
|View full text |Cite
|
Sign up to set email alerts
|

Network motifs for translator stylometry identification

Abstract: Despite the extensive literature investigating stylometry analysis in authorship attribution research, translator stylometry is an understudied research area. The identification of translator stylometry contributes to many fields including education, intellectual property rights and forensic linguistics. In a two stage process, this paper first evaluates the use of existing lexical measures for the translator stylometry problem. Similar to previous research we found that using vocabulary richness in its tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The order of the experiments is the following: 1) Subsection IV-A presents the results of the experiments performed on the Don Quixote corpus. We contrast them with the results in [21]. 2) Then, in Subsection IV-B, we present the results for the experiments on the Ibsen parallel corpus (i.e., the two translations of the play Ghosts) and compare them with the results on the same corpus of [20].…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The order of the experiments is the following: 1) Subsection IV-A presents the results of the experiments performed on the Don Quixote corpus. We contrast them with the results in [21]. 2) Then, in Subsection IV-B, we present the results for the experiments on the Ibsen parallel corpus (i.e., the two translations of the play Ghosts) and compare them with the results on the same corpus of [20].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The two most recent works, which are also closer to what we attempt here, are [20] and [21]. The authors of both papers use the methodology suggested by Baker [5] of using parallel corpora-same source text translated by different people into the same target language.…”
Section: A Previous Work On Translated Textsmentioning
confidence: 89%
See 3 more Smart Citations